Rahaidi Bamboo Music Therapy For Concentration In Adults with Autism - Fahdi Hasan; Dinda Satya Upaja Budi; Arthur S. Nalan (PANTUN: Jurnal Ilmiah Seni Budaya, 2025)
This research aims to highlight the effects of using the Rahaidi bamboo musical instrument in increasing the concentration of adults with autism at the Special Individuals Cultural Foundation (YBUIS) Bandung. The research was conducted using qualitative methods with an action research approach based on the Lin S. Norton model. The techniques used include observation, interviews, literature study, as well as five research steps: identifying problems, solutions, implementation, evaluation, and modification. Data analysis was carried out using an organological approach (Sue Carole DeVale) and concentration theory (Santrock), with data validation through the ITDEM model which involves triangulation and data reduction. The research results show that the use of Rahaidi bamboo musical instruments can increase four types of attention, namely Selective Attention, Sustained Attention, Executive Attention, and Divided Attention. The process is divided into three stages: beginner, intermediate, and advanced, including assessment, design, therapy implementation, recording, and evaluation. This research proves that there is a significant increase in all aspects of attention in adult individuals with autism after therapy using Rahaidi bamboo music. These results confirm that a tailored approach using musical instruments can be an effective therapeutic tool in supporting the development of concentration in adults with autism.